2022
DOI: 10.1186/s40824-022-00294-2
|View full text |Cite
|
Sign up to set email alerts
|

P800SO3-PEG: a renal clearable bone-targeted fluorophore for theranostic imaging

Abstract: Background Due to the deep tissue penetration and reduced scattering, NIR-II fluorescence imaging is advantageous over conventional visible and NIR-I fluorescence imaging for the detection of bone growth, metabolism, metastasis, and other bone-related diseases. Methods Bone-targeted heptamethine cyanine fluorophores were synthesized by substituting the meso-carbon with a sulfur atom, resulting in a bathochromic shift and increased fluorescence inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…1 C), indicating that cRGD-ZW800-PEG was rapidly decomposed upon NIR irradiation. Similar to ZW800-PEG, the overall electron density on the heptamethine chain of cRGD-ZW800-PEG increases due to the π-donation from the sulfur atom, which makes the heptamethine chain easier to undergo the oxidative addition with reactive singlet oxygen species [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…1 C), indicating that cRGD-ZW800-PEG was rapidly decomposed upon NIR irradiation. Similar to ZW800-PEG, the overall electron density on the heptamethine chain of cRGD-ZW800-PEG increases due to the π-donation from the sulfur atom, which makes the heptamethine chain easier to undergo the oxidative addition with reactive singlet oxygen species [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Choi and coworkers integrated the specific segment of phosphonates into the non‐delocalized framework of heptamethine cyanine, resulting in a set of bone‐targeted NIR fluorescent probes 26 – 28 (Figure 7a). [56] Probes 26 – 28 exhibit a strong affinity for HAP and CP, enhancing their specificity for bone targeting, achieving a SBR surpassing 3.5.…”
Section: Fluorescent Probes For Bonementioning
confidence: 99%
“…28−33 Choi et al utilized bisphosphonates to target hydroxyapatite and developed a small molecular fluorophore (emission: 1000 nm) for bone imaging. 34 More specifically, in the NIR-IIb window (1500− 1700 nm), light scattering is further reduced and autoluminescence is diminished, allowing for deeper penetration. 35−38 Zeng et al reported a poly(acrylic acid)-modified rare-earth nanoparticle at an emission wavelength of 1525 nm, displaying high affinity for bone.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Compared to the visible light and near-infrared I (NIR-I, 700–900 nm), NIR-II (1000–1700 nm) offers higher spatial resolution, greater penetration depths into biological substrates, lower optical absorption and scattering, and minimal tissue autofluorescence. Hence, NIR-II imaging is increasingly researched due to its immense potential in preclinical studies and clinical applications. Despite the limited studies currently conducted, NIR-II imaging undoubtedly holds significant potential for real-time monitoring and a more precise diagnosis of skeletal disorders. Recently, researchers developed rare-earth-based nanoparticles, gold nanoclusters, and small conjugated polymer nanoparticles for bone imaging, respectively. Choi et al utilized bisphosphonates to target hydroxyapatite and developed a small molecular fluorophore (emission: 1000 nm) for bone imaging . More specifically, in the NIR-IIb window (1500–1700 nm), light scattering is further reduced and autoluminescence is diminished, allowing for deeper penetration. Zeng et al reported a poly­(acrylic acid)-modified rare-earth nanoparticle at an emission wavelength of 1525 nm, displaying high affinity for bone .…”
Section: Introductionmentioning
confidence: 99%